ANALISIS BIAYA RELEVAN SEBAGAI ALAT PENGAMBILAN KEPUTUSAN PENERIMAAN ATAU PENOLAKAN PESANAN KHUSUS - Hernanik, Nova Dwi (Fakultas Ekonomi Universitas Wisnuwardhana, 2020)
Abstrak. PT. X is a service company that manufactures Tires, Carpets, andHoses. This study aims to determine the application of cost classification, but alsoto find out relevant cost analysis on this company, and evaluate the impact on thecompany's profit and loss in accepting or rejecting special orders. The method ofresearch conducted by the author is to conduct research directly to the company,observe company activities, study documents related to the object of research,and also conduct interviews with relevant parties. In addition, the authors alsoconducted a literature study so that it could assist the writer in calculating therelevant costs in making decisions whether to accept or reject special orders. Theresults showed that PT. X has not yet classified the production costs properly, sothat management decision making is also not right, where many companies rejectspecial orders, without analyzing them first. From the findings of existing problems,the authors suggest that the company should evaluate the production costsincurred in the company on a regular basis so as to obtain accurate and adequatecost data. Companies should also make a separation between fixed costs andvariable costs because this is quite important in providing relevant information tocompanies to build long-term competitive advantage.Keywords: Relevant Costs of Decision Making Tools, Receiving or DecliningSpecial Orders.